Artificial Intelligence Methods for Modelling Tremor Mechanisms - Groznik, Vida (Informatica, 2020)
The paper summarises a Doctoral Thesis in which we focus on two main goals: (1) building models for differentiation between three most common tremors: Parkinsonian, essential and mixed type tremor and (2) development of a novel method for attribute visualisation on series.